Parboiled rice bran subjected to prolonged storage for meat quail feeding - Farias, Nadja Naiara Pereira; Freitas, Ednardo Rodrigues; Xavier, Regina Patrícia de Souza; Braz, Nádia de Melo; Tavares, Thais Cruz Lopes; Figueiredo, Carlos Weiber Silva; Fernandes, Danilo Rodrigues; Nascimento, Germano Augusto Jerônimo do (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the oxidative stability of parboiled rice bran (PRB) during storage and the effects of its use on meat quail feeding. Two hundred forty‑five animals, with seven days of age, of both sexes, were used, distributed in a completely randomized design, with five treatments in a 2x2+1 factorial arrangement and seven replicates of seven chicks. The following treatments were evaluated: control diet, without PRB; and inclusion levels of 10 and 20% of 180-day-storaged PRB (SPRB) or of new PRB (NPRB) in the control diet. There was lipid oxidation of PRB during storage, the acid index was 4.25 and 63.50 (% as oleic acid) and the peroxide index was 15.64 and 38.28 meq kg-1 for NPRB and SPRB, respectively. The inclusion of PRB resulted in lower dry matter and nitrogen digestibility and in higher metabolizable energy value of feed when compared to the control diet. The inclusion of 20% SPRB resulted in lower metabolizable energy of feed than the addition of NPRB. The inclusions did not influence performance, carcass traits, relative weights of the liver and pancreas, and bone growth and quality. The SPRB, although rancid, can be used as feed for meat quail at levels up to 20% inclusion.